Problems associated with menstruation among medical students: a cross sectional study - Shantha, A.; V., Roselin; V., Srisanthanakrishnan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Medical students are at high risk for developing menstrual irregularities due to their lifestyle, food pattern and exercise habits. Also, majority of the menstrual disorders are preventable by changing better lifestyle, early diagnosis and treatment. Hence this study was conducted with the objective of addressing the menstrual disorders and associated problems among the medical students. Methods: The cross-sectional study was conducted by the department of obstetrics and gynaecology, at Sri Muthukumaran Medical College Hospital and Research Institute, among the first, second- and third-year female students who are doing their MBBS course in the same institute, during the month of December 2019. A total of hundred students were included in the study. Data was collected using a proforma and analysis was done using Statistical Package for Social Sciences (SPSS) version 17. Results: Menstrual cycle periodicity was irregular among 17% of participants. Dysmenorrhoea, mid cycle pain, heavy menstrual bleeding was noted among 27%, 19% and 11% respectively. Also 10% of students reported sickness absenteeism due to menstrual disorders. Conclusions: Adolescent students should be educated on the importance of physical and mental health in terms of healthy food habits and regular physical exercise to overcome the menstrual disorders and to enjoy healthy reproductive period.